Pengaruh pengembangan karir, efikasi diri (self-efficacy) dan hubungan baik atasan dan bawahan (leader-member exchange) terhadap kinerja karyawan (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2017)
ABSTRACTRahmat Saputro trinandes, 2016. The influence of career development, self-efficacy and leader-member Exchage the performance of employees of PT Astra International Tbk Daihatsu Branch Samarinda. (Guided by Dr. Hj. Yana Ulfah, SE., M.Si, Ak, CA., M.Si and Dr. Gusti Noorlitria Achmad, SE., MM)This study aimed to test whether career development, self-efficacy and leader-member Exchage significant influence on employee performance. The independent variables in this study is career development, self-efficacy and leader-member Exchage. While the dependent variable is employee performance. This research was conducted at PT Astra International Tbk Daihatsu Samarinda Branch consisting of 34 persons as respondents.This research is quantitative. The data collection is done by collecting a questionnaire to examine career development, self-efficacy and leader-member Exchage partially. Analysis of data using multiple linear regression. These results indicate the career development variables have a significant influence on employee performance, whereas the variable self-efficacy and leader-member variables have a significant influence on employee performance. Keywords: career development, self-efficacy and leader-member Exchage and performance.